Military nursing research : bibliographies (National Academy Press, 1996)
Description for testing purposes.
Prepared to accompany: The program for research in military nursing: progress and future direction. 1996.
Keywords: Military nursing -- Abstracts.; Military nursing.; Nursing -- Research.; Military Nursing; Nursing Research; Soins infirmiers militaires -- Résumés analytiques.; Soins infirmiers militaires.; Soins infirmiers -- Recherche.; HISTORY -- Military -- Biological & Chemical Warfare.; Nursing -- Research; Military nursing; Abstracts; headings.; abstracts (summaries); Abstracts.; Résumés analytiques.